Unknown Input Observer for a Doubly Fed Induction Generator Subject to Disturbances - Samir Abdelmalek; Linda Barazane; Abdelkader Larabi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper deals with the problem design of an unknown input observer (UIO) for a Doubly Fed Induction Generator (DFIG) subject to disturbances. These disturbances can be considered as unknown inputs (UI). The state space model of the DFIG is obtained from the voltage equations of the stator and rotor. Then, this latter is used for the design of an unknown input observer (UIO) in order to estimate both the state and the unknown inputs of the DFIG. Furthermore, the UIO gains are computed by solving a set of linear matrix inequalities (LMIs). Simulations results are given to show the performance and the effectiveness of the proposed method.